A Facile Strategy for Synergistic Integration of Dynamic Covalent Bonds and Hydrogen Bonds to Surmount the Tradeoff between Mechanical Property and Self‐Healing Capacity of Hydrogels. Issue 2 (9th December 2020) - Ma, Minglei; Yang, Jumin; Ye, Zhanpeng; Dong, Anjie; Zhang, Jinwei; Zhang, Jianhua
Abstract: The self‐healable hydrogels have attracted increasing attention due to their promising potential for ensuring the durability and reliability of hydrogels. However, they still face a serious challenge to achieve a positive balance between mechanical and healing performance, especially for the room‐temperature autonomous self‐healable hydrogels. Herein, a simple but efficient strategy to fabricate a kind of dynamic boronate and hydrogen bonds dual‐crosslinked double network (DN) hydrogel based on a UV‐initiated one‐pot in situ polymerization of N ‐acryloyl glycinamide (NAGA) in polyvinyl alcohol‐borax slime is reported. The obtained PN‐ x /PB hydrogels, especially with high content of PNAGA, are shown to possess high mechanical strength, high toughness, and fatigue‐resistance properties as well as excellent self‐healability at room temperature (nearly 88% self‐healing efficiency based on the strain compression test), due to the dynamic DN structure, and the combination of the adaptable and reconfigurable dynamic boronate bonds and hydrogen bonds. Considering the easily available materials and simple preparation process, this novel strategy should offer not only a kind of dynamic DN hydrogel with robust mechanical performance and high self‐healing capability, but also enrich the methodological toolbox for synergistic integration of dynamic covalent bonds and hydrogen bonds to surmount the tradeoff between mechanical properties and self‐healing capacity of hydrogels. Abstract : The self‐healable hydrogels often suffer from a low mechanical performance. Herein, a kind of dynamic boronate bonds and hydrogen bonds dual‐crosslinked double network hydrogels are prepared from readily available starting materials and without sophisticated molecular design. The obtained hydrogels are demonstrated to possess high mechanical strength, high toughness, and fatigue‐resistance property as well as excellent self‐healability at room temperature.